PROSES MORFOLOGIS PADA CERPEN LING DALAM ANTOLOGI LING KARYA I KOMANG ALIT JULIARTHA - Parameswari, A.A Istri Laksmi (Prosiding Seminar Nasional Bahasa Ibu; Vol 2 No 1 (2025): Prosiding Seminar Nasional Bahasa Ibu 2024/2025, 2025)
Language as a communication tool is used by speakers to convey ideas to other people. Conveying ideas through language is found in literary works, one of which is short stories. In a short story, every word is chosen carefully to build the storyline. Therefore, morphological analysis can help reveal how word formation influences the meaning the author wants to convey. The aim of this research is to describe the morphological processes of affixation, reduplication and compounding used by the author in Ling's short stories in the Ling Anthology. The research method used in this research is descriptive qualitative. Data collection used the observation method using note-taking techniques. The listening method is done by reading Ling's short story in its entirety and repeatedly. The note-taking technique is used so that after reading things that cover the morphological processes in Ling's short stories can be studied.  The results of this research found morphological processes of affixation, reduplication and compounding found in Ling's short stories. The morphological process of affixation found consists of prefixes, suffixes and confixes. The reduplication process found consists of complete repetition, repetition with partial affixes, and repetition with phoneme changes.